2014
DOI: 10.1074/jbc.m113.526814
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor-1α (HIF-1α) Protein Diminishes Sodium Glucose Transport 1 (SGLT1) and SGLT2 Protein Expression in Renal Epithelial Tubular Cells (LLC-PK1) under Hypoxia

Abstract: Background: Hypoxia regulates the transport systems expression in kidney cells. Results: Expression of SGLT1 and SGLT2 is diminished in LLC-PK 1 cells exposed to low oxygen concentrations. Conclusion: HIF-1␣ modified expression of the renal transporters SGLT1 and SGLT2 in LLC-PK 1 cells. Significance: HIF-1 regulates the expression of glucose transport in LLC-PK 1 cells, and this mechanism may be involved in the adaptation of kidney cells under reductions conditions in pO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 44 publications
(65 reference statements)
3
38
1
Order By: Relevance
“…Our samples were from matched groups of people with T2DM and controls with well-preserved renal function (Table 1). 24 Recently, a net decrease in the expression of the glucose transporters SGLT1 and SGLT2 under hypoxic conditions, and an inverse relationship with HIF-1α expression, have been reported in cultured epithelial tubular cells 8 ; in the present study, we confirm this observation for the first time in humans, thereby providing a putative molecular explanation for the reduced renal SGLT2 and SGLT1 expression observed in people with diabetes. 23 Diabetic nephropathy has been associated with progressive chronic hypoxia and tubulo-interstitial fibrosis; a biomarker of this condition is HIF-1α, whose expression is usually increased in diabetic kidneys.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our samples were from matched groups of people with T2DM and controls with well-preserved renal function (Table 1). 24 Recently, a net decrease in the expression of the glucose transporters SGLT1 and SGLT2 under hypoxic conditions, and an inverse relationship with HIF-1α expression, have been reported in cultured epithelial tubular cells 8 ; in the present study, we confirm this observation for the first time in humans, thereby providing a putative molecular explanation for the reduced renal SGLT2 and SGLT1 expression observed in people with diabetes. 23 Diabetic nephropathy has been associated with progressive chronic hypoxia and tubulo-interstitial fibrosis; a biomarker of this condition is HIF-1α, whose expression is usually increased in diabetic kidneys.…”
Section: Discussionsupporting
confidence: 87%
“…6 Another point deserving further investigation is the relative weight of SGLT1 and SGLT2 in tubular glucose reabsorption, given that SGLT2-selective inhibitors only block glucose reabsorption by 30% to 40%. 8 The aim of the present study, therefore, was to quantify the expression of both SGLT2 and SGLT1, their cognate basolateral transporters, GLUT2 and GLUT1, and the transcriptional regulator of SGLTs in renal tissue obtained from people with T2DM and a group of well-matched people without diabetes. Even less is known about the regulatory pathways of this system; hypoxia-inducible factor-1α (HIF-1α), a transcription factor induced by low oxygen, has recently been shown to downregulate the expression of SGLT1 and SGLT2 under hypoxic conditions in a model of pig epithelial tubular cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers reported that hypoxia‐induced death of renal epithelial cells in the acute phase of renal ischemia does not depend on functional HIF‐1 in primary cultured mouse renal tubular epithelial cell (Biju et al, ). In addition, Zapata‐Morales et al, () reported that hypoxia increased HIF‐1α while decreased SGLT1 and SGLT2 in renal epithelial tubular cell (LLC‐PK1). Our result showed the decreased SGLTs along with decreased HIF‐1α, which suggests that relationship between HIF‐1α and SGLTs expressions depend on experimental condition such as experimental model and cell type et al In this study, OGT siRNA treatment for inhibition of Sp1 O‐GlcNAcylation and Sp1 siRNA significantly reduced GlcN‐induced HIF‐1α protein expression under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, phosphorylation of the cytokine transforming growth factor β1 and the downstream transcription factor smad3 increased SGLT2 protein expression in human kidney proximal tubular cells [66]. Under pathological conditions, both cobalt chloride and low oxygen pressure induced hypoxia in LLC-PK1 cells increased hypoxia-inducible factor-1α expression and was associated with reduced SGLT1 and SGLT2 expression [67 ▪ ]. The mechanism remains elusive, but might involve reducing the work load under hypoxic conditions or could be an effect secondary to reduced sodium/potassium-ATPase activity.…”
Section: Regulation Of Sodium-glucose Cotransportermentioning
confidence: 99%